ANALYSIS OF VIRTUAL WATER USE ON FOOD CONSUMPTION USING THE WATER FOOTPRINT CONCEPT IN CITY OF BANDUNG - HAIDIR (NIM: 25312026), MUHAMMAD
In producing food takes a lot of water from the beginning of the process to the final product,) that large amounts of freshwater are required throughout the supply chain of a product until the moment of consumption. So that the consumption of food also spend a lot of water contained in food (virtual water). Therefore it takes the water footprint concept to calculate the water use indirectly in the individual or group food consumptions in City of Bandung. Primary data collected by questionnaire survey in Mandalajati District, Coblong District and Sumur Bandung District with sample size of 70, divided to five category: carbohydrate; animal product; vegetables and fruits; soybean curd and fermented soybean; coffee, tea and sugar. Secondary data collected by observation and interview,and data from government agencies related to study and other source. Analysis method use linear regression and correlation analysis. Calculation method based on The Water footprint Assessement Manual. Questionnaire instrument has high validity (0.946) and has a middle realibility (0.426). The value of food consumption in Mandalajati District, Coblong District and Sumur Bandung District are 669 m3/capita/year, 723 m3/capita/year and 741m3/capita/year respectively. Generally average water footprint of food consumption in Bandung is 715 m3/capita/year or reach 1713 million m3/year. Animal product has a largest consumption water footprint (286 m3/capita/year) or 40 % from the total water footprint of food consumption. There is a logarithmic relationship pattern between income level with water footprint of food consumption. Correlation analysis shown that the income level has a very strong correlation (0.99) with water footprint of food consumption value with significance α=1% and α=5%. The projection of food consumption water footprint in 2050 with no improvement of technology will increase by 90%, while with low technology improvement, middle technology improvement and high technology improvement will increase 79%, 74% and 72% respectively. Water footprint of food consumption value (indirect use) 10 times greater than the value of water consumption water footprint (direct use). Relation between ecological footprint and water footprint of food consumption shows that Bandung requires an area of 5.34 million Ha and 1713 million m3/year to produce the food to consumed. Blue water scarcity index (WS blue) is above 100 percent, which means not sustainable. In other words, the blue water availability in Bandung could not sustain the value of the blue water footprint of food consumption in Bandung. Bandung should 'importing' virtual water as much as 1613 million m3/year in the form of food product from other areas to meet the food consumption needs. Water footprint of food consumption can be reduced at the consumer level, product level, business level and government's role by water use management directly and indirectly